Application of a Robotic Arm in Assisting Disinfection Before Venipuncture Needle Insertion - Hsu, Wen-Tung; Chen, Cheng-Ho (International Journal of Psychosocial Rehabilitation, 2020)
Robots have been widely used in various medical practices ranging from complicated neurosurgery to patient rehabilitation in recent years. They are playing ever more important roles in medical institutions and of great help to medical staff in the jobs they are doing. However, in one of the most frequently performed procedure, venipuncture, application of robots or other automatic devices remains largely unseen. The procedure, though may not be as complicated as a neurosurgery, still requires trained and experienced personnel and is inherently risky. Studies have shown that percutaneous injuries are the most common occupational injuries for medical personnel and the costs are high for medical institutions. Venipuncture consists of several steps. In this paper, the application of a robotic arm in assisting disinfection before needle injection is studied. The ultimate goal is to develop a fully automatic venipuncture system.